Angiotensin II-induced TLR4 mediated abdominal aortic aneurysm in apolipoprotein E knockout mice is dependent on STAT3. (October 2015) - Qin, Zhexue; Bagley, Jessamyn; Sukhova, Galina; Baur, Wendy E.; Park, Ho-Jin; Beasley, Debbie; Libby, Peter; Zhang, Yali; Galper, Jonas B.
Abstract: Abdominal Aortic Aneurysm (AAA) is a major cause of mortality and morbidity in men over 65 years of age. Male apolipoprotein E knockout (ApoE −/− ) mice infused with angiotensin II (AngII) develop AAA. Although AngII stimulates both JAK/STAT and Toll-like receptor 4 (TLR4) signaling pathways, their involvement in AngII mediated AAA formation is unclear. Here we used the small molecule STAT3 inhibitor, S3I-201, the TLR4 inhibitor Eritoran and ApoE −/− TLR4 −/− mice to evaluate the interaction between STAT3 and TLR4 signaling in AngII-induced AAA formation. ApoE −/− mice infused for 28 days with AngII developed AAAs and increased STAT3 activation and TLR4 expression. Moreover, AngII increased macrophage infiltration and the ratio of M1 (pro-inflammatory)/M2 (healing) macrophages in aneurysmal tissue as early as 7–10 days after AngII infusion. STAT3 inhibition with S3I-201 decreased the incidence and severity of AngII-induced AAA formation and decreased MMP activity and the ratio of M1/M2 macrophages. Furthermore, AngII-mediated AAA formation, MMP secretion, STAT3 phosphorylation and the ratio of M1/M2 macrophages were markedly decreased in ApoE −/− TLR4 −/− mice, and in Eritoran-treated ApoE −/− mice. TLR4 and pSTAT3 levels were also increased in human aneurysmal tissue. These data support a role of pSTAT3 in TLR4 dependent AAA formation and possible therapeutic roles for TLR4 and/or STAT3 inhibition in AAA. Highlights: By using AngII induced AAA formation in the ApoE -/- mice, we demonstrate that AngII mediated AAA is in part dependent on the STAT3 via TLR4. We offer evidence that small molecule STAT3 inhibitor, S3I-201, and the TLR4 inhibitor, Eritoran, markedly attenuate AAA formation in this model. We demonstrate the role of STAT3 and TLR4 in macrophage infiltration and the ratio of M1/M2 macrophages during AAA formation.